2019
DOI: 10.1111/jgh.14569
|View full text |Cite|
|
Sign up to set email alerts
|

Extracorporeal shock wave lithotripsy is safe and effective for geriatric patients with chronic pancreatitis

Abstract: Background and Aim Pancreatic extracorporeal shock wave lithotripsy (P‐ESWL) is a first‐line treatment for chronic pancreatitis (CP) patients with pancreatic stones. However, the performance of P‐EWSL in geriatric patients remains unclear. We aimed to evaluate the safety and efficacy of P‐ESWL for them. Methods This prospective study was conducted in painful CP patients who underwent P‐ESWL. Patients aged over 65 years were included in geriatric group; patients aged under 65 years were assigned to control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…and prospectively enrolled. The detailed information of Changhai CP Database (version number 2.1, Shanghai, China) has been reported in our previous researches [15][16][17][18][19][20][21][22] . The exclusion criteria were as follows: pancreatic cancer diagnosed within 2 years after the diagnosis of CP 23 , groove pancreatitis 24 , autoimmune pancreatitis, and CP patients with distinct etiologies (including alcoholic, abnormal anatomy of pancreatic duct, hereditary, post-traumatic, and hyperlipidemic).…”
mentioning
confidence: 99%
“…and prospectively enrolled. The detailed information of Changhai CP Database (version number 2.1, Shanghai, China) has been reported in our previous researches [15][16][17][18][19][20][21][22] . The exclusion criteria were as follows: pancreatic cancer diagnosed within 2 years after the diagnosis of CP 23 , groove pancreatitis 24 , autoimmune pancreatitis, and CP patients with distinct etiologies (including alcoholic, abnormal anatomy of pancreatic duct, hereditary, post-traumatic, and hyperlipidemic).…”
mentioning
confidence: 99%
“…6,8,9 P-ESWL disintegration success rate using electromagnetic P-ESWL lithotripters for pancreatic head stones ranges from 10.17% to 81.9%. 6,10,11 A prospective Chinese study reported more fragmented stones among 214 pancreatic head stones. 12 Several studies have indicated that the presence of a single stone and the absence of MPD stricture are prognostic factors for complete stone removal.…”
Section: Discussionmentioning
confidence: 99%
“…Extracorporeal shock wave lithotripsy (ESWL) is a highly effective treatment method for pancreatic stone fragmentation, especially for stones larger than 5 mm. 63 , 64 Previous retrospective cohort studies have shown that ESWL is safe and effective for CP patients, even for those who are geriatric, 65 pediatric, 66 postoperative, 67 or with pancreatic pseudocysts. 68 However, the evidence from RCT on the safety and efficacy of ESWL on pancreatic stones is still of scarcity.…”
Section: Endoscopic Treatmentmentioning
confidence: 99%